Comparative analysis of three-dimensional chromosomal architecture identifies a novel fetal hemoglobin regulatory element. - Huang, P; Keller, C; Giardine, B; Grevet, J; Davies, J; Hughes, J; Kurita, R; Nakamura, Y; Hardison, R; Blobel, G (Cold Spring Harbour Laboratory Press, 2017)
Chromatin structure is tightly intertwined with transcription regulation. Here we compared the chromosomal architectures of fetal and adult human erythroblasts and found that, globally, chromatin structures and compartments A/B are highly similar at both developmental stages. At a finer scale, we detected distinct folding patterns at the developmentally controlled β-globin locus. Specifically, new fetal stage-specific contacts were uncovered between a region separating the fetal (γ) and adult (δ and β) globin genes (encompassing the HBBP1 and BGLT3 noncoding genes) and two distal chromosomal sites (HS5 and 3'HS1) that flank the locus. In contrast, in adult cells, the HBBP1-BGLT3 region contacts the embryonic ε-globin gene, physically separating the fetal globin genes from the enhancer (locus control region [LCR]). Deletion of the HBBP1 region in adult cells alters contact landscapes in ways more closely resembling those of fetal cells, including increased LCR-γ-globin contacts. These changes are accompanied by strong increases in γ-globin transcription. Notably, the effects of HBBP1 removal on chromatin architecture and gene expression closely mimic those of deleting the fetal globin repressor BCL11A, implicating BCL11A in the function of the HBBP1 region. Our results uncover a new critical regulatory region as a potential target for therapeutic genome editing for hemoglobinopathies and highlight the power of chromosome conformation analysis in discovering new cis control elements.